N-oxide sensing in Pseudomonas aeruginosa: expression and preliminary characterization of DNR, an FNR–CRP type transcriptional regulator. (1st February 2005) - Rinaldo, S.; Giardina, G.; Brunori, M.; Cutruzzolà, F.
Abstract : In denitrifying bacteria, the concentration of NO is maintained low by a tight control of the expression and activity of nitrite and NO reductases. Regulation involves redox-linked transcription factors, such as those belonging to the CRP-FNR (cAMP receptor protein–fumarate and nitrate reductase regulator) superfamily, which act as oxygen and N-oxide sensors. Given that few members of this superfamily have been characterized in detail, we have cloned, expressed and purified the dissimilative nitrate respiration regulator from Pseudomonas aeruginosa . To gain insights on the structural properties of the dissimilative nitrate respiration regulator, we have also determined the aggregation state of the purified protein and its ability to bind hydrophobic compounds such as 8-anilino-1-naphthalenesulphonic acid.